2020
DOI: 10.7554/elife.52549
|View full text |Cite|
|
Sign up to set email alerts
|

c-Maf restrains T-bet-driven programming of CCR6-negative group 3 innate lymphoid cells

Abstract: RORγt+ group 3 innate lymphoid cells (ILC3s) maintain intestinal homeostasis through secretion of type 3 cytokines such as interleukin (IL)−17 and IL-22. However, CCR6- ILC3s additionally co-express T-bet allowing for the acquisition of type 1 effector functions. While T-bet controls the type 1 programming of ILC3s, the molecular mechanisms governing T-bet are undefined. Here, we identify c-Maf as a crucial negative regulator of murine T-bet+ CCR6- ILC3s. Phenotypic and transcriptomic profiling of c-Maf-defici… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 67 publications
2
33
0
Order By: Relevance
“…This intra-subset plasticity is driven by the cytokine milieu and the activity of particular TFs, and these may lead to different ILC3 compositions in distinct tissues [96]. Recent studies have shown that the TF c-Maf serves as a regulator of ILC3-ILC1 plasticity in the intestine [99][100][101]. Comparison of c-Maf-deficient ILC3 from Rorc cre Maf fl/fl mice with ILC3 from controls revealed that c-Maf restrains T-bet expression in CCR6 − ILC3 and thereby prevents the acquisition of a type 1 phenotypea mechanism that appears to be regulated by IL-1β, IL-18, and Notch signals [100].…”
Section: Ilc3 In Micementioning
confidence: 99%
See 1 more Smart Citation
“…This intra-subset plasticity is driven by the cytokine milieu and the activity of particular TFs, and these may lead to different ILC3 compositions in distinct tissues [96]. Recent studies have shown that the TF c-Maf serves as a regulator of ILC3-ILC1 plasticity in the intestine [99][100][101]. Comparison of c-Maf-deficient ILC3 from Rorc cre Maf fl/fl mice with ILC3 from controls revealed that c-Maf restrains T-bet expression in CCR6 − ILC3 and thereby prevents the acquisition of a type 1 phenotypea mechanism that appears to be regulated by IL-1β, IL-18, and Notch signals [100].…”
Section: Ilc3 In Micementioning
confidence: 99%
“…Recent studies have shown that the TF c-Maf serves as a regulator of ILC3-ILC1 plasticity in the intestine [99][100][101]. Comparison of c-Maf-deficient ILC3 from Rorc cre Maf fl/fl mice with ILC3 from controls revealed that c-Maf restrains T-bet expression in CCR6 − ILC3 and thereby prevents the acquisition of a type 1 phenotypea mechanism that appears to be regulated by IL-1β, IL-18, and Notch signals [100]. Thus, cytokines in the small intestine can regulate ILC3-ILC1 plasticity by activating distinct TFs to adapt to the local tissue environment.…”
Section: Ilc3 In Micementioning
confidence: 99%
“…21,69 The balance between RORγt and T-bet is regulated by the TF c-Maf, which repressed T-bet expression by binding to the promoter and therefore suppressing the type 1 program in ILC3s. 70,71 NK CELLS Immune recognition strategies used by NK cells Immune recognition in both the innate and adaptive immune system relies to a large extent on the interaction between immunoreceptors and the corresponding ligands. Moreover, such immunoreceptors in most cases detect non-self peptides with respect to the T cell receptor (TCR) or B cell receptor (BCR), or ligands recognizing a broad biochemical spectrum in case of pattern recognition receptors.…”
Section: Ilc Developmentmentioning
confidence: 99%
“…2 ]. Hence, Notch could act on the c-Maf/T-bet balance as a cell-intrinsic brake in the type 1 effector acquisition by NCR + ILC3s [ 70 ]. During intestinal inflammation, a dysregulation of the Notch pathway might disrupt this balance and lead to pathogenic functions.…”
Section: Notch and Ilc Developmentmentioning
confidence: 99%